Peran Digital Payment, Literasi Keuangan, dan Gaya Hidup terhadap Perilaku Keuangan Mahasiswa - Ermasanti Mahmudah; Vicky Oktavia; Diana Puspitasari; Rudi Kurniawan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The rapid development of financial technology, financial literacy, and student lifestyles can influence financial behavior. The purpose of this study was to analyze the influence of digital payments, financial literacy, and lifestyle on students' financial behavior. A quantitative method was used, involving 150 respondents from the Faculty of Economics and Business, Dian Nuswantoro University, and was taken through a purposive sampling technique. Data were collected from questionnaires and analyzed using SPSS version 25. The results showed that digital payments and financial literacy had a positive effect on financial behavior, while lifestyle had a negative effect on financial behavior. These findings imply that increasing financial knowledge and planning, including saving habits, controlling consumptive behavior, and wise use of fintech services, effectively shape students' financial attitudes.